Origins of Intelligence: The Evolution of Cognitive Development in Monkeys, Apes, and Humans - Parker, Sue Taylor; McKinney, Michael L. (Johns Hopkins University Press, 1999)
Since Darwin’s time, comparative psychologists have searched for a good way to compare cognition in humans and nonhuman primates. In Origins of Intelligence, Sue Parker and Michael McKinney offer such a framework and make a strong case for using human development theory (both Piagetian and neo-Piagetian) to study the evolution of intelligence across primate species. Their approach is comprehensive, covering a broad range of social, symbolic, physical, and logical domains, which fall under the all-encompassing and much-debated term intelligence.A widely held theory among developmental psychologists and social and biological anthropologists is that cognitive evolution in humans has occurred through juvenilization—the gradual accentuation and lengthening of childhood in the evolutionary process. In this work, however, Parker and McKinney argue instead that new stages were added at the end of cognitive development in our hominid ancestors, coining the term adultification by terminal extension to explain this process.Drawing evidence from scores of studies on monkeys, great apes, and human children, this book provides unique insights into ontogenetic constraints that have interacted with selective forces to shape the evolution of cognitive development in our lineage.
Keywords: Animal intelligence; Cognition; Cognition in animals; Comparative; Evolution.; Genetic psychology; Psychology